Uptake and release of amino acids in the fetal-placental unit in human pregnancies - Holm, Maia Blomhoff; Bastani, Nasser Ezzatkhah; Holme, Ane Moe; Zucknick, Manuela; Jansson, Thomas; Refsum, Helga; Mørkrid, Lars; Blomhoff, Rune; Henriksen, Tore; Michelsen, Trond Melbye (PloS one, 2017)
The current concepts of human fetal-placental amino acid exchange and metabolism are mainly based on animal-, in vitro- and ex vivo models. We aimed to determine and assess the paired relationships between concentrations and arteriovenous differences of 19 amino acids on the maternal and fetal sides of the human placenta in a large study sample. This cross-sectional in vivo study included 179 healthy women with uncomplicated term pregnancies. During planned cesarean section, we sampled blood from incoming and outgoing vessels on the maternal (radial artery and uterine vein) and fetal (umbilical vein and artery) sides of the placenta. Amino acid concentrations were measured by liquid chromatography-tandem mass spectrometry. We calculated paired arteriovenous differences and performed Wilcoxon signed-rank tests and Spearman's correlations. In the umbilical circulation, we observed a positive venoarterial difference (fetal uptake) for 14 amino acids and a negative venoarterial difference (fetal release) for glutamic acid (p<0.001). In the maternal circulation, we observed a positive arteriovenous difference (uteroplacental uptake) for leucine (p = 0.005), isoleucine (p = 0.01), glutamic acid (p<0.001) and arginine (p = 0.04) and a negative arteriovenous difference (uteroplacental release) for tyrosine (p = 0.002), glycine (p = 0.01) and glutamine (p = 0.02). The concentrations in the maternal artery and umbilical vein were correlated for all amino acids except tryptophan, but we observed no correlations between the uteroplacental uptake and the fetal uptake or the umbilical vein concentration. Two amino acids showed a correlation between the maternal artery concentration and the fetal uptake. Our human in vivo study expands the current insight into fetal-placental amino acid exchange, and discloses some differences from what has been previously described in animals. Our findings are consistent with the concept that the fetal supply of amino acids in the human is the result of a dynamic interplay between fetal and placental amino acid metabolism and interconversions.